Using Bayesian methods to evaluate the diagnostic performance of blood-based diagnostic tests for American cutaneous leishmaniasis and Chagas disease in rural Panamanian dogs in the absence of a gold standard - Kimberly Archbold; Vanessa Pineda; José E. Calzada; Azael Saldaña; Adelys Reina; Alberto Cumbrera; Ayesha Rodríguez; Chystrie Rigg; Caleb Hawkins; Daniel Mendieta; John P. Schmidt; Julie Velásquez Runk; et al. (Veterinary Parasitology, 2026)

Development of a New Aerosol Delivery System for Administering Aerosol Surfactant Therapy to Preterm Infants Through a Laryngeal Mask Airway - Sarah C. Strickler; Caleb J. Dalton; Felicia G. Hall; Dale R. Farkas; Mohammad A. M. Momin; Robert M. DiBlasi; Michael Hindle; P. Worth Longest (AAPS PharmSciTech, 2026)

Hybrid particulate matter generated by lava-ignited wildfires at the Litli-Hrútur 2023 eruption, Iceland - Laura Wainman; Evgenia Ilyinskaya; Melissa Anne Pfeffer; Penny E. Wieser; David Damby; James B. McQuaid; Celine Mandon; Enikö Bali; Josefa Sepulveda-Araya; Richard Walshaw; Caleb Hall; Stuart Micklethwaite; et al. (Science of The Total Environment, 2026)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Clean co-combustion of glycerol and methanol blends using a novel fuel-flexible injector - Timothy Hall; Derek Williams; S M Rafiul Islam; Ishaan Patel; Caleb Chakmakjian; Lulin Jiang (Fuel, 2024)

Fully Implanted Prostheses for Musculoskeletal Limb Reconstruction After Amputation: An In Vivo Feasibility Study - Patrick T. Hall; Samantha Z. Bratcher; Caleb Stubbs; Rebecca E. Rifkin; Remi M. Grzeskowiak; Bryce J. Burton; Cheryl B. Greenacre; Stacy M. Stephenson; David E. Anderson; Dustin L. Crouch (Annals of Biomedical Engineering, 2021)

Combining passive integrated transponder tags with conventional T‐bar tags to improve tag reporting rates in a rock lobster trap fishery - Stewart D. Frusher; David Hall; Paul Burch; Caleb Gardner (New Zealand Journal of Marine and Freshwater Research, 2009)
Tag reporting rate is an important parameter required for estimating fishing and natural mortality in fished populations. It is an extremely difficult parameter to estimate and can vary both during the fishing season and between fishing years. Improving tag reporting rates has been identified as a cost‐effective way of improving precision in fishing and natural mortality estimates derived from tagging data. In this study we evaluated the use of passive integrated transponder (PIT) tags to improve tag reporting rates in a lobster (Jasus edwardsii) trap fishery. To minimise the risk of PIT tag ingestion by consumers, we tested insertion of the PIT tag into the base of the antennae, the base of the walking leg, and the base of the telson. The base of the antennae proved to be the best option for lobster health although impacts were observed at all tag insertion sites. We further developed and tested a hybrid tag that combined a conventional external T‐bar tag with a PIT tag embedded within the shaft. PIT tag scanners were positioned in bottlenecks in the capture process so that all lobsters retained on board the vessel were passed through a scanner. Thus, the tag reporting rate was expected to be 100% for the subsample of the fleet fitted with scanners when scanners were operational. Scanner malfunction was a major issue and further engineering solutions are required to ensure that scanners are reliable when working in harsh marine conditions such as on‐board fishing vessels. Advantages of the hybrid tag are: the ability to be detected by both automatic detectors and fishers; known tag‐induced mortality and tag loss rates from previous research; and PIT tagging without risk of human ingestion.